2020
DOI: 10.1105/tpc.20.00155
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Plant Enhancers and Their Constituent Elements by STARR-seq in Tobacco Leaves

Abstract: A high-throughput assay in transiently transformed tobacco leaves identifies enhancers, characterizes their functional elements and detects condition-specific enhancer activity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 61 publications
6
77
0
Order By: Relevance
“…To maximize the use of natural variation, and for synthetic biology to realize its full potential, deeper knowledge of regulatory modules is paramount to facilitate crop improvement. Numerous reporter assays are now being developed and implemented for the identification and functional characterization of CRMs ( Inoue and Ahituv, 2015 ; Ricci et al, 2019 ; Sun et al, 2019 ; Jores et al, 2020 ), but there is still a need for more epigenome maps from many different cell types and growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To maximize the use of natural variation, and for synthetic biology to realize its full potential, deeper knowledge of regulatory modules is paramount to facilitate crop improvement. Numerous reporter assays are now being developed and implemented for the identification and functional characterization of CRMs ( Inoue and Ahituv, 2015 ; Ricci et al, 2019 ; Sun et al, 2019 ; Jores et al, 2020 ), but there is still a need for more epigenome maps from many different cell types and growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In maize, both proximal and distal ACRs were found to show a general enhancement of activity, relative to randomly selected regions with similar features (Ricci et al, 2019). On the other hand, a modified version of STARR-seq using transient transfection in tobacco leaves found that four known plant enhancers gave the strongest transcriptional output when placed immediately upstream of a minimal promoter and were not active when placed in the 3'UTR of the reporter gene (Jores et al, 2020). Further studies are needed to tease out the functional determinants and optimal architecture of the various classes of regulatory elements.…”
Section: Genome-wide Identification Of Cis-regulatory Regionsmentioning
confidence: 98%
“…In plants, these operational definitions are even more vague; however, studies have begun to tease out some common trends. Plant adapted versions of massively parallel promoter and enhancer reporter assays such as self-transcribing active regulatory region sequencing (STARR-seq; Ricci et al, 2019;Jores et al, 2020), show that many ACRs are capable of enhancing gene expression (Ricci et al, 2019). Traditional STARR-seq works by inserting fragments either from randomly sheared genomic sequence, BAC libraries, or small fragments such as those from ATAC-seq and placing them downstream of a cassette containing a minimal promoter fused to GFP (Arnold et al, 2013).…”
Section: Genome-wide Identification Of Cis-regulatory Regionsmentioning
confidence: 99%
“…These cell types are suitable for the use of direct transformation methods such as electroporation, gene gun bombardment, and microinjection. However, generation of these cell lines is often inefficient depending on the species used, produces fragile cells, and may not behave as an intact plant would ( Jores et al, 2020 ). A recent study utilized an industrially scalable delivery of self-replicating viral vectors to transform a variety of crop species, such as tomato, potato, and spinach, with successful alterations to reproduction, stature, and drought tolerance ( Torti et al, 2021 ).…”
Section: Opportunities and Obstacles In Using Plants As A Production Platformmentioning
confidence: 99%